A mutation in a Rhodobacter capsulatus gene encoding an integration host factor-like protein impairs in vivo hydrogenase expression. - Toussaint, B (1991)
A gene capable of encoding a protein sharing 45% identical amino acids with the alpha subunit of the integration host factor (IHF) of Escherichia coli was isolated from the photosynthetic bacterium Rhodobacter capsulatus strain B10 by complementation of a hydrogenase-deficient (Hup-) mutant, IR4. A DNA fragment of 274 base pairs containing an IHF binding consensus sequence, isolated from the promoter region of the hydrogenase structural genes (hupSL), was shown by gel retardation assays to bind the IHF protein from E. coli. The product of the R. capsulatus gene was shown to bind specifically to the 274-base-pair DNA fragment from the hupSL promoter. By analogy to the E. coli himA gene, which encodes the alpha subunit of IHF, the gene complementing the IR4 mutant was named himA of R. capsulatus. The wild-type himA gene, cloned in plasmid pBO2, was introduced into the IR4 strain and shown to restore, in trans, hydrogenase activity and autotrophic growth in the mutant. In IR4, a C----T transition mutation had replaced Arg-8 by Cys-8. Gel mobility shifts of the 274-base-pair DNA fragment, not observed with the himA gene product of IR4, were restored with extracts from IR4(pBO2) cells, containing the himA gene on the recombinant plasmid pBO2.